Adenosine A2A Receptors in Secondary Progressive Multiple Sclerosis: A [11C]TMSX Brain PET Study. Issue 9 (September 2013) - Rissanen, Eero; Virta, Jere R; Paavilainen, Teemu; Tuisku, Jouni; Helin, Semi; Luoto, Pauliina; Parkkola, Riitta; Rinne, Juha O; Airas, Laura
In this study, positron emission tomography (PET) imaging with a radioligand to adenosine A2A receptors (A2AR)—a potent regulator of inflammation—was used to gain insight into the molecular alterations in normal-appearing white matter (NAWM) and gray matter (GM) in secondary progressive multiple sclerosis (SPMS). Normal-appearing white matter and GM, despite seeming normal in conventional mangnetic resonance imaging (MRI), are important loci of widespread inflammation, neuronal damage, and source of progressive disability in multiple sclerosis (MS). Dynamic PET imaging using A2AR-specific [ 11 C]TMSX and brain MRI with diffusion tensor imaging were performed to eight SPMS patients and seven healthy controls. Distribution volumes ( V T ) of [ 11 C]TMSX were analyzed from 13 regions of interest using Logan plot with arterial plasma input. The SPMS patients had significantly increased [ 11 C]TMSX- V T in NAWM compared with controls (mean (s.d.): 0.55 (± 0.08) vs. 0.45 (± 0.05); P = 0.036). Both the increased V T and the decreased fractional anisotropy (FA) in NAWM were associated with higher expanded disability status scale (EDSS) scores ( P = 0.030 and P = 0.012, respectively), whereas the T2-lesion load of SPMS patients did not correlate with EDSS. This study shows, that A2ARs are increased in the brain of SPMS patients, and that [ 11 C]TMSX-PET provides a novel approach to learn about central nervous system pathology in SPMS in vivo.